(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the era of pervasive social media, college graduates’ intention to return to their hometowns for entrepreneurship is shaped by the complex interplay of multiple forces. This study adopts a mixed-method approach combining fuzzy-set Qualitative Comparative Analysis (fsQCA) and Necessary Condition Analysis (NCA) to examine how seven key components of the entrepreneurial ecosystem—government policy, rural infrastructure, employment situation, innovation and entrepreneurship education, entrepreneurial competency, emotional attachment, and family support—collectively influence return-home entrepreneurial intention (RHEI) in China. The findings show that no single element constitutes a necessary condition for high RHEI. Rather, specific configurations of these elements jointly foster strong entrepreneurial intentions. Unlike previous studies, we find that a favorable employment situation does not necessarily hinder return-home entrepreneurship; however, without the support of other ecosystem elements, high employment alone fails to motivate return-home action. Furthermore, social media emerges as an implicit yet powerful mediator, amplifying the influence of emotional attachment and family support. This study provides practical insights for promoting rural entrepreneurship among graduates and enhancing sustainable regional development.